Universal aspects of light halo nuclei - Frederico, T.; Delfino, A.; Tomio, Lauro [UNESP]; Yamashita, Marcelo Takeshi [UNESP] (Elsevier B.V., 2012)
The theoretical status on universal aspects of weakly-bound neutron-rich light nuclei are reviewed, considering few-body approaches. We focus the review on the low-energy properties of light halo nuclei that can be treated within two- and three-body approaches (with one- and two-neutron halos), which are dominated by s-wave two-body interactions. The representative works studying the large two-neutron halos in light exotic nuclei with short-range interactions show that the general properties associated with the halo neutrons are model independent.and obey scaling laws, which are functions of the low-energy observables of the neutron-neutron and neutron-core subsystems, with one additional scale that represents the physics of the three-body system at short-ranges. The scaling laws for the s-wave two-neutron halos are identified with limit-cycles in a renormalized zero-range three-body model. The necessary basic concepts for interpreting the physics of large halos, and also to treat the zero-range interaction in few-body systems, are given. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Halo nuclei; Few-body systems; Binding energies and masses; Faddeev equation